2022
DOI: 10.3390/jof8020158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Sources on the Production of Volatile Organic Compounds by Fusarium verticillioides

Abstract: The aim of the present study was to evaluate the effect of different carbon sources on the hydrocarbon-like volatile organic compounds (VOCs) of Fusarium verticillioides strain 7600 through a Principal Component Analysis approach, and to explore their diesel potential by using data from the literature. The fungus was cultivated in GYAM culture medium, and five carbon sources were evaluated: glucose, sucrose, xylose, lactose, and fructose. The VOCs were collected using a close-loop apparatus and identified thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…2,4-dimethylheptane has been reported as a VOC in Ficus tikoua [ 41 ] and fungi [ 42 , 43 ]. The production of 2,4-dimethylheptane by Fusarium verticillioides has also been documented [ 44 ]. Jia et al [ 45 ] demonstrated that the exogenous application of jasmonic acid enhanced the 4-methyloctane content in grapefruit and induced resistance against Botrytis cinerea .…”
Section: Discussionmentioning
confidence: 99%
“…2,4-dimethylheptane has been reported as a VOC in Ficus tikoua [ 41 ] and fungi [ 42 , 43 ]. The production of 2,4-dimethylheptane by Fusarium verticillioides has also been documented [ 44 ]. Jia et al [ 45 ] demonstrated that the exogenous application of jasmonic acid enhanced the 4-methyloctane content in grapefruit and induced resistance against Botrytis cinerea .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, dimethyl disulfide was found in the sample infected with F. sambucinum (Table S1 and Table 3). Apart from terpenes, other fungal origin compounds were found, including hydrocarbons, acids, ketones, and alcohols [7,[50][51][52][53][54]. In the samples inoculated with C. coccodes and R. solani, a methylated derivative of benzene, i.e., 1,2,4-trimethylbenzene was detected, which was not found in other samples, including the control.…”
Section: Colletotrichum Coccodesmentioning
confidence: 99%
“…These organics were identified as volatile compounds produced by Muscodor suthepensis [56], Alternaria alternata [50], and Rhizoctonia solani and Trichoderma viride [57]. [56]; P [58,67] M [7,50,63]; P [61] M [7,52,61] M [7] M [53]; P [58] All compound numbers refer to the order in Table S1. * M-microbial, P-plant; # unknow origin.…”
Section: Colletotrichum Coccodesmentioning
confidence: 99%
“…Moreover, the comparison of dry-cleaning emissions with the organic solvent demonstrated that nonane seemingly increased from 14% to 35%, while decane and undecane seemingly decreased from 34% to 31% and from 25% to 13%. The compounds with low boiling points are generally characterized by the ability to evaporate into the atmosphere, mixing with air, and accumulation ability [ 50 ]. Besides that, Wang et al, (2013) [ 51 ] have previously confirmed that the evaporation rate of the solvent varied according to the difference in its boiling point.…”
Section: Resultsmentioning
confidence: 99%